Deterioration of muscle force and contractile characteristics are early pathological events in spinal and bulbar muscular atrophy mice - Anna L. Gray; Leonette Annan; James R. T. Dick; Albert R. La Spada; Michael G. Hanna; Linda Greensmith; Bilal Malik (The Company of Biologists, 2020)
Spinal and bulbar muscular atrophy (SBMA), also known as Kennedy's Disease, is a late-onset X-linked progressive neuromuscular disease, which predominantly affects males. The pathological hallmarks of the disease are selective loss of spinal and bulbar motor neurons, accompanied by weakness, atrophy and fasciculations of bulbar and limb muscles. SBMA is caused by a CAG repeat expansion in the gene that encodes the androgen receptor (AR) protein. Disease manifestation is androgen dependent and results principally from a toxic gain of AR function. There are currently no effective treatments for this debilitating disease. It is important to understand the course of the disease in order to target therapeutics to key pathological stages. This is especially relevant in disorders such as SBMA, for which disease can be identified before symptom onset, through family history and genetic testing. To fully characterise the role of muscle in SBMA, we undertook a longitudinal physiological and histological characterisation of disease progression in the AR100 mouse model of SBMA. Our results show that the disease first manifests in skeletal muscle, before any motor neuron degeneration, which only occurs in late-stage disease. These findings reveal that alterations in muscle function, including reduced muscle force and changes in contractile characteristics, are early pathological events in SBMA mice and suggest that muscle-targeted therapeutics may be effective in SBMA. This article has an associated First Person interview with the first author of the paper.